Dynamical forecast model skill in the Colombian agricultural context, joint work between Fedearroz, IDEAM, CIAT-CCAFS and University of Leeds - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
WRF-model implementation required adjustment of the soil layer, and of land cover, using the IGAC dataset. Scripts have been developed, as a generation of the necessary files for using into the rice model. Depending on the FEDEARROZ experience, model results will also be used for maize agro-climatic forecasts by FENALCE.